Language in uniform language analysis and training for defence and policing purposes - De Silva Joyce, Helen; Thomson, Elizabeth A. (Cambridge Scholars Publishing, 2015)
Language in Uniform: Language Analysis and Training for Defence and Policing Purposes brings together a collection of papers that reflect the diverse work being done in the often overlooked LSP fields of defence, security and policing. As language learning is increasingly becoming an integral part of life in uniform, this volume extends the theoretical and practical understanding of LSP and acknowledges the ground-breaking work that has been, and continues to be, done with this approach in language teaching and assessment for defence, security and law enforcement purposes.